2014
DOI: 10.1128/mcb.00622-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Immunoproteasome as a Novel Regulator of Skeletal Muscle Differentiation

Abstract: While many of the molecular details of myogenesis have been investigated extensively, the function of immunoproteasomes (iproteasomes) in myogenic differentiation remains unknown. We show here that the mRNA of i-proteasome subunits, the protein levels of constitutive and inducible proteasome subunits, and the proteolytic activities of the 20S and 26S proteasomes were significantly upregulated during differentiation of skeletal muscle C2C12 cells. Knockdown of the i-proteasome catalytic subunit PSMB9 by short h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 60 publications
0
66
0
Order By: Relevance
“…Fluorescence were read for 60 min at 10 min intervals at λecc = 360; λemm = 465, gain 60. Results were expressed as RFU/min/mg protein using angular coefficient of interpolate line [21].…”
Section: Proteasome Activity Assaymentioning
confidence: 99%
“…Fluorescence were read for 60 min at 10 min intervals at λecc = 360; λemm = 465, gain 60. Results were expressed as RFU/min/mg protein using angular coefficient of interpolate line [21].…”
Section: Proteasome Activity Assaymentioning
confidence: 99%
“…49,53,54 We found that the immunoproteasome subunit LMP7 (b5i) is localized mainly to the cytosol as expected and that the subunit PSMB5 (b5) of the constitutive proteasome is localized mainly to the nucleus. As the constitutive proteasome also degrades proteins in the cytosol, it must be transported from the nucleus to the cytosol on demand.…”
Section: Discussionmentioning
confidence: 61%
“…The increased levels of oxidized proteins suggest that many enzymes are likely to be oxidized and have lower enzymatic activity. Increased levels of oxidized proteins in I79N hearts could result from the decreased proteasome activity because the proteasome is involved in degrading oxidized proteins (36). It is also possible that the increased levels of oxidized proteins in these stressed hearts are due to increased energy production.…”
Section: Proteins Involved In Metabolism-mentioning
confidence: 99%
“…The reaction was initiated by adding the specific substrate at a final concentration of 100 M. Final concentrations of bort and specific fluorogenic substrates for each proteolytic proteasome subunit, respectively were: ␤1 -100 M bort, Z-Leu-Leu-Glu-MCA (Peptide Institute, 3179-v), ␤5 -10 M bort, Suc-Leu-Leu-Val-Tyr-AMC (Bachem, Bubendorf, Switzerland, I-1395). These assays have been previously described (35,36).…”
Section: Familial Hypertrophic Cardiomyopathy (Fhc)mentioning
confidence: 99%
See 1 more Smart Citation